The area-based management tools coordination between IMO and BBNJ agreement regimes and its implications on vessel pollution control - Wang, Jinpeng; Zhang, Yiwei (Frontiers in Marine Science, 2024)
The International Maritime Organization (IMO), as a specialized agency of the United Nations responsible for the safety and security of international shipping and the prevention of pollution from ships, has applied two main area-based management tools (ABMTs): the “Special Areas” established under the MARPOL 73/78; and the “Particularly Sensitive Sea Areas” (PSSAs) established under the IMO resolutions. The new Agreement under the United Nations Convention on the Law of the Sea on the Conservation and Sustainable Use of Marine Biological Diversity of Areas beyond National Jurisdiction (BBNJ agreement) stipulates the establishment of a comprehensive system of ABMTs to conserve and sustainably use areas beyond national jurisdiction. Strengthening coordination in the use of ABMTs established by the IMO and the BBNJ Agreement is important for vessel pollution control in the high seas. The IMO is a stakeholder for relevant proposals and consultations on proposals regarding the establishment of ABMTs in the BBNJ Agreements, and can provide information on the implementation of them. The Conference of the Parties (COPs) to the BBNJ Agreement can also make recommendations to the IMO and its parties to promote the adoption of special areas and PSSAs. This article respectively elaborates on the practices and effect of ABMTs of the IMO and explores the relevant rules of the BBNJ agreement and their enforcement. Then this article discusses the possible approaches for the ABMTs coordination between the IMO and the BBNJ agreement regimes and their implications on vessel pollution Control in the high seas. Overall, relevant rules of the BBNJ agreement shall be interpreted and applied in a manner that does not undermine relevant legal instruments of the IMO. Meanwhile, it is necessary to promote cooperation and coordination between the COPs to the BBNJ Agreement and the IMO under the idea of conserving ecosystem integrity, gradually forming a normal cooperation and information exchange mechanism.